Experimental Study on Damage and Gas Migration Characteristics of Gas-Bearing Coal with Different Pore Structures under Sorption-Sudden Unloading of Methane - Gang Wang; Yangyang Guo; Chang’ang Du; Lulu Sun; Zhiyuan Liu; Yue Wang; Jianjun Cao (Geofluids)
Coal and gas outburst is one of the most serious hazards in underground mine operations. In this paper, we explored the damage and gas seepage characteristics of gas-bearing coal samples with different pore structures under methane sorption-sudden unloading conditions using a self-developed experimental apparatus. The results show that (1) the deformation of coal samples can be divided into three stages, namely, pressure-increase-induced compression, sorption-induced expansion, and sudden-unloading-induced deformation or failure stage; (2) with the increase of the number of diffusion pores in the coal sample, the amount of gas sorption gradually increases and the expansion and failure of coal samples become more obvious; (3) in the experiment, the damage of coal samples is mainly along the axial direction and rarely along the radial direction; (4) the radial strain is always greater than the axial strain.